Biomarkers of Guillain-Barré Syndrome: Some Recent Progress, More Still to Be Explored - Ying Wang; Shuang Sun; Jie Zhu; Li Cui; Hong-Liang Zhang (Mediators of Inflammation)
Guillain-Barré syndrome (GBS), the axonal subtype of which is mainly triggered by C. jejuni with ganglioside-mimicking lipooligosaccharides (LOS), is an immune-mediated disorder in the peripheral nervous system (PNS) accompanied by the disruption of the blood-nerve barrier (BNB) and the blood-cerebrospinal fluid barrier (B-CSF-B). Biomarkers of GBS have been extensively explored and some of them are proved to assist in the clinical diagnosis and in monitoring disease progression as well as in assessing the efficacy of immunotherapy. Herein, we systemically review the literature on biomarkers of GBS, including infection-/immune-/BNB, B-CSF-B, and PNS damage-associated biomarkers, aiming at providing an overview of GBS biomarkers and guiding further investigations. Furthermore, we point out further directions for studies on GBS biomarkers.